Weberbauerella chilensis (Fabaceae: Papilionoideae), a new species from the Atacama Desert, Chile - Saldivia, Patricio; Faúndez, Luis (Phytotaxa, 2014)
A new legume species, Weberbauerella chilensis, from the Andean foothills in the Tarapacá region in Chile, is described and illustrated. This species represents the first record of the genus in Chile and the Southern Cone of South America and is the third species described for the genus. Weberbauerella chilensis resembles  W. brongnartioides from Peru, but differs primarily in its smaller size, fewer leaflets and habitat conditions.